1994
DOI: 10.1038/hdy.1994.168
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between DNA structural variation and activities of P elements in P and Q strains of Drosophila melanogaster

Abstract: To characterize the relationship between P element activities and their structures, we cloned P elements from genomic libraries of three isogenic P and 0 strains derived from natural populations in Japan. These P elements were mapped with BamHl, A vail and Pstl and were classified by their size. The majority of P elements cloned were classified as either complete or relatively small P elements rather than medium size. The numbers of full length (2.9 kb) P elements per haploid genome of NP280 (P), AK194 (weak P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Other internally deleted elements also occur, but in lower numbers, as deduced from the signal intensity of the bands between those of 2.2 and 0.42 kb. The predominance of full-sized P plus KP elements in the genomes of most populations around the world has been pointed out by Itoh and collaborators (Itoh and Boussy, 2002;Itoh et al, 2001), based on their own surveys or on other authors (Boussy et al, 1988;Nitasaka and Yamazaki, 1994;Bonnivard and Higuet, 1999;French et al, 1999;Itoh et al, 2001;Itoh and Boussy, 2002). Itoh and Boussy (2002) wondered whether this could be the final equilibrium state of the D. melanogaster genomes in nature, and suggested that further surveys of wild populations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Other internally deleted elements also occur, but in lower numbers, as deduced from the signal intensity of the bands between those of 2.2 and 0.42 kb. The predominance of full-sized P plus KP elements in the genomes of most populations around the world has been pointed out by Itoh and collaborators (Itoh and Boussy, 2002;Itoh et al, 2001), based on their own surveys or on other authors (Boussy et al, 1988;Nitasaka and Yamazaki, 1994;Bonnivard and Higuet, 1999;French et al, 1999;Itoh et al, 2001;Itoh and Boussy, 2002). Itoh and Boussy (2002) wondered whether this could be the final equilibrium state of the D. melanogaster genomes in nature, and suggested that further surveys of wild populations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Of 293 isofemale lines from 45 localities examined, only eight lines (2.7%) lacked full-size P and four lines (1.4%) lacked KP elements; thus FP+KP predominance was seen in 96% of the lines (Itoh et al, 1999). Another line of evidence for FP+KP predominance comes from a molecular study by Nitasaka and Yamazaki (1994), who isolated all genomic P elements from three genomes from a natural population of Japan and found more than one copy each of full-size and KP elements in all three genomes examined. A single detailed analysis of a North American strain, π2, found seven complete P and two KP elements in its genome, but also 19 other defective P elements (O'Hare et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…1). Both 5' and 3' regions may be affected whereas in D. melanogaster the P derivative elements described are generally deleted in the 3' region (O'Hare et a!., 1992; Nitasaka & Yamazaki, 1993). In several cases, the deletion seems to include all or a part of the inverted terminal repeat (ITR).…”
Section: Molecular Propertiesmentioning
confidence: 99%
“…melanogaster such deletions have not been described (O'Hare ci' al., 1992;Nitasaka & Yamazaki, 1993). This could be fortuitous or it may result from differences in the transposition mechanism as well as in selective pressure on such derivative P elements.…”
mentioning
confidence: 99%